P-195 Mucosal Microbiota that Breach the Intestinal Epithelial Barrier—A Step Towards Identifying Potential Pathogens in IBD. (March 2016) - Dheer, Rishu; Davies, Julie; Quintero, Maria Alejandra; Santaolalla, Rebeca; Deshpande, Amar; Kerman, David; McCauley, Jacob; Abreu, Maria
Abstract : Background: Interaction between host intestinal microbiota and the immune system plays a vital role in initiation, progression and severity of IBD. Although numerous deep sequencing studies have suggested dysbiosis in IBD, identifying specific bacteria that are responsible for disease susceptibility or severity have remained a challenge. We hypothesized that in IBD only a subpopulation of the commensal microbiota would breach the epithelial barrier into the lamina propria. To test this, we examined the microbiota associated with lamina propria phagocytes in IBD patients. Methods: Biopsy samples were collected from IBD patients. Lamina propria phagocytes were isolated from the biopsies using magnetic-activated cell sorting (MACS). 16S rRNA gene sequencing was performed on mucosal biopsies and sorted phagocytic cells. Results: IBD patients exhibited considerable inter-individual variation in their mucosal and phagocyte-associated microbiota. PCoA based on Bray-Curtis distance matrices revealed that the microbiota associated with lamina propria phagocytes is distinct from mucosal microbiota in IBD patients. To identify the bacterial taxa that were significantly associated with lamina propria phagocytes, we examined the relative abundance of bacterial taxa in mucosal tissues and phagocytic cells of IBD patients. Linear discriminant analysis effect size (LEfSe) analysis indicated that the bacterial species belonging to phylum Proteobacteria were enriched in the phagocyte-associated microbiota whereas species belonging to phylum Bacteroidetes and Verrucomicrobia were enriched in mucosal microbiota of IBD patients. Conclusions: The results of this study suggest that phagocyte associated microbiota comprises a population of commensal microbiota that preferentially pass through the epithelial barrier. Further studies will be needed to address the colitogenic potential of these bacteria.